2015
DOI: 10.1246/bcsj.20150340
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Dispersion of “Super-Growth” Single-Walled Carbon Nanotubes Using a Copolymer of Naphathalene Diimide and Poly(dimethylsiloxane)

Abstract: The dispersion of carbon nanotubes is a key issue for maximizing their performance in many applications. Here we describe the design and synthesis of an efficient dispersant for the so-called “super-growth” single-walled carbon nanotubes (SG-SWNTs) to provide a stable and homogeneous dispersion in typical organic solvents simply by sonication. The synthesized dispersant is a copolymer composed of a naphthalene diimide and poly(dimethylsiloxane), and the dispersions were characterized using visible absorption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…39 It was claimed that a naphthalene diimide and poly(dimethylsiloxane) based dispersant was synthesized to enhance the agglomeration of the SWCNTs in the matrix. 40 It was reported that the bending modulus of the binary nanocomposite showed an improvement of about onethird compared to the neat composite. 41 In addition, the carbon ber surface characteristics were also found to have a signicant effect on the bending properties of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…39 It was claimed that a naphthalene diimide and poly(dimethylsiloxane) based dispersant was synthesized to enhance the agglomeration of the SWCNTs in the matrix. 40 It was reported that the bending modulus of the binary nanocomposite showed an improvement of about onethird compared to the neat composite. 41 In addition, the carbon ber surface characteristics were also found to have a signicant effect on the bending properties of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…Between the two approaches developed so far for preparing SWNTs dispersions, noncovalent functionalization is considered to be superior to the covalent one in terms of preserving the conjugated structure and intrinsic properties of SWNTs. Therefore, a number of researchers have concentrated on developing novel and efficient dispersants, including surfactants, biomolecules, aromatic compounds, and polymers, ,, for noncovalent functionalization of SWNTs. On the other hand, the means employed to achieve noncovalent functionalization have been mostly limited to bath and probe type sonication. ,, Although these liquid-phase sonication based techniques are sufficient for debundling and dispersing SWNTs in various solvents in the presence of dispersant, they suffer from either low concentration or low yield (<60 μg / mL or <15%, respectively) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a number of researchers have concentrated on developing novel and efficient dispersants, including surfactants, biomolecules, aromatic compounds, and polymers, ,, for noncovalent functionalization of SWNTs. On the other hand, the means employed to achieve noncovalent functionalization have been mostly limited to bath and probe type sonication. ,, Although these liquid-phase sonication based techniques are sufficient for debundling and dispersing SWNTs in various solvents in the presence of dispersant, they suffer from either low concentration or low yield (<60 μg / mL or <15%, respectively) . Furthermore, the presence of solvent may make the concentration less controllable and less precise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, other CE materials, such as PbS, Cu 2 S, CoS, CoS/CuS, NiS, carbon, ZnO/metal sulfides, and Cu 2 S-reduced graphene oxide composites, have been inspected for their higher electrocatalytic activity towards the reduction of the polysulfide redox couple 14 15 16 17 18 19 20 21 . Carbon nanotubes (CNTs) are attractive candidates with high electrical conductivity, large surface area, and low density, making them candidates for applications in various fields, such as microelectronics, energy, and biotechnology 22 23 24 25 26 . Recently, multiwall carbon nanotubes (MWCNTs) were proposed as an efficient CE material in QDSSCs to suppress the charge transfer resistance at the CE/electrolyte interface and achieve higher efficiency (4.67%) than CuS CE (3.67%) 27 .…”
mentioning
confidence: 99%